(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Financial administration is whose discipline is responsible for the planning, organization and control of financial resources, that is, it is responsible for decision-making on financing, investments, savings and budgets, etc. Well, its implications consist of obtaining an operational function dedicated to the structure, liquidity management and financial assets in this matter. In order to understand it, it is necessary to emphasize its purpose, this is planning, which will be in charge of those long and short-term economic agreements, in order to reduce risks and thereby increase the value of the company. Taking into account the development of the market, therefore, it includes all financial investment decisions, such as financing, programming and control of investment projects, investment policies, among others. The objectives of financial management mainly include the maintenance of resources, optimal understanding and management of risks (mainly in investments), seeking to maximize profits or income, and finally, improving the use of already existing financial resources. whether from an individual or a company. This article will allow us to know the basic knowledge of "the theoretical implications of financial administration", in order to implement an action plan when making investments, and with it the adequate planning for the improvement of expenses, in such a way create a good budget and maximize profits. The financial resources of the company are fundamental, hence the idea that a good management of these leads to success, within the financial administration the efficient study of money is managed.